The role of women’s perceived empowerment in sustaining mobile banking engagement: Evidence from rural Indonesia - Charnila, Dwi; Winjaniatun, Siti Novrianti; Simanjuntak, Evi Rinawati (The Economics and Finance Letters, 2026)
Digital financial inclusion aims to ensure equitable access to financial services; however, rural women continue to face structural, cultural, and psychological barriers that limit their ability to adopt and sustain mobile banking usage. This study extends the Theory of Planned Behavior (TPB) by incorporating Perceived Women’s Empowerment (PWE) as both a direct predictor and a moderating variable influencing long-term digital financial engagement. A quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) was conducted on data collected from 420 rural women mobile banking users in Indonesia. The measurement and structural models demonstrated strong reliability, validity, and significant relationships among all hypothesized paths. Attitude toward technology (β = 0.199), subjective norm (β = 0.164), and perceived behavioral control (β = 0.487) significantly predicted behavioral intention. Behavioral intention strongly influenced continuous usage (β = 0.470), which subsequently had a major impact on digital financial inclusion (β = 0.742). Perceived women’s empowerment directly affected usage patterns (β = 0.141) and significantly strengthened the relationship between behavioral intention and continuous usage. The findings highlight empowerment as a critical behavioral catalyst that enables rural women to move from basic digital access toward meaningful and sustained financial engagement. The proposed framework emphasizes the need for gender-sensitive financial inclusion strategies that build psychological readiness and agency, allowing policymakers and practitioners to design more inclusive and effective digital financial systems for developing regions.